The Oral Hydroalcoholic Extract of Licorice for Management of Mild to Moderate Coronavirus Disease-19 Patients: A Double-Blind Randomized Clinical Trial - Adeleh Jeddi; Amir Hooshang Mohammadpour; Milad Iranshahy; Ali Moradi; Batool Zarei (Research Center for Rational Use of Drugs (RCRUD), 2023)
Background: Licorice is proposed as a treatment option for coronavirus disease-19 (COVID-19) by inhibiting the virus binding, penetration and replication; it also modulates various cellular signaling pathways. In this double-blind randomized-controlled trial, efficacy of Licorice hydroalcoholic extract oral formulation has been evaluated in patients with mild-moderate COVID-19in an outpatient clinic. Methods: A total of 40 mild to moderate outpatient Covid-19cases were randomly assigned into either Licorice or placebo groups (n=20 in each). Patients in Licorice group were given 700 mg capsules of hydroalcoholic extract of Licorice, trice a day for 2 weeks, while controls were given placebo capsules that were filled with Avicel (microcrystalline cellulose). Blood samples were collected from all participants before starting the medication and on days three, seven, and 14 for laboratory parameters including quantitative C-reactive protein (CRP), WBCs, lymphocytes, and neutrophils counts. The clinical symptoms were also recorded. Results: Our results showed that Licorice extract significantly decreased the frequency of cough on day seven (P=0.004) and the frequency of dyspnea on day three (P=0.02). No significant differences were found in the frequency of nausea, diarrhea, body pain, sore throat, runny nose, dizziness, lethargy, and loss of taste or smell between the two groups. Patients in Licorice group showed significantly higher oxygen saturations on days three, seven, and 14. Other laboratory parameters did not show any changes between the two groups. Conclusion: licorice extract improved some clinical symptoms such as cough and dyspnea while only increased the oxygen saturation. Further studies with larger sample sizes at different stages of Covid-19are suggested.